1998
DOI: 10.1074/jbc.273.6.3517
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Human Class Mu Glutathione S-Transferase Gene Cluster and the GSTM1Deletion

Abstract: A partial physical map has been constructed of the human class Mu glutathione S-transferase genes on chromosome 1p13.3. The glutathione S-transferase genes in this cluster are spaced about 20 kilobase pairs (kb) apart, and arranged as 5 -GSTM4-GSTM2-GSTM1-GSTM5-3 . This map has been used to localize the end points of the polymorphic GSTM1 deletion. The left repeated region is 5 kb downstream from the 3 -end of the GSTM2 gene and 5 kb upstream from the beginning of the GSTM1 gene; the right repeated region is 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 38 publications
1
116
0
5
Order By: Relevance
“…Typically, the individual genes for each GST class are clustered together on the same chromosome (23)(24)(25). The fact that no other related sequences were found neither in this chromosomal region nor in other part of the genome seems to indicate that hGSTK1 is the only representative in this GST family in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the individual genes for each GST class are clustered together on the same chromosome (23)(24)(25). The fact that no other related sequences were found neither in this chromosomal region nor in other part of the genome seems to indicate that hGSTK1 is the only representative in this GST family in humans.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the mutation is a result of an unequal crossing over of the M1 and M2 loci (Xu et al, 1998), which are in close physical proximity and share 99% nucleotide sequence identity (Pearson et al, 1993). The frequency of GTSM1*0 individuals is approximately 67% in Australians, 50% in Caucasians and 22% in Nigerians (Smith et al, 1995).…”
Section: Mu Classmentioning
confidence: 99%
“…GSTM1 is coded by a gene located on chromosome 1p13.3 [11]. The homozygous deletion (null genotype) of the GSTM1 gene results in the total absence of a functional gene product, and thus a total absence of the respective enzyme activity.…”
Section: Introductionmentioning
confidence: 99%